Evaluating the role of the exchange rate in monetary policy reaction function of advanced and emerging market economies - Nikola Fabris; Milena Lazić (Journal of Central Banking Theory and Practice, 2022)
The subject of this paper is the evaluation of monetary policy reaction function on panel data of 37 world economies, both advanced and emerging markets, during the period of 1995Q1 - 2018Q3. The paper aims to evaluate the role and importance of the exchange rate in monetary policy reaction function depending on the level of economic development. For this purpose, a relevant set of unbalanced panel data was formed with a balanced relationship between developed and emerging market economies. The methodology of empirical research is based on the econometric assessment of monetary policy reaction function within which the central bank adjusts its key policy rate to the dynamics of inflation, output gap and fluctuations of the real effective exchange rate. The research results confirm the hypothesis that the exchange rate represents a statistically significant variable only in the monetary policy reaction function of emerging market economies. In contrast, adequate specification of developed economies' monetary policy rule includes only standard macroeconomic fundamentals - inflation and output gap.
Keywords: C820; E430; E520; 330; monetary policy reaction function; Taylor rule; panel data analysis; exchange rate; developed countries; emerging market economies